Why does sweat lead to the development of itch in atopic dermatitis?. Issue 12 (3rd July 2019) - Murota, Hiroyuki; Yamaga, Kosuke; Ono, Emi; Murayama, Naoya; Yokozeki, Hiroo; Katayama, Ichiro
Abstract: Sweating plays an important role in maintaining temperature homeostasis in humans. However, under certain circumstances, sweat can cause itching. For example, when excessive sweat accumulates on the skin surface for a long period, miliaria can develop and cause itching. Subjects with dermatoses, such as atopic dermatitis (AD), suffer from itch when exposed to heat or psychological stresses, which are also known perspiration stimuli. Recently, some mechanisms of sweat‐induced itch have been revealed. For instance, attenuated sweating ability is observed in subjects with AD, causing heat retention, skin dryness, and high susceptibility to itch. Furthermore, the decreased tight junction of the sweat gland in AD leads to sweat leakage in the dermis, which could be designated as a "sweat endocrine response" and may be the cause of tingling itch during sweating. Additionally, metabolomic analysis of sweat from patients with AD revealed that glucose concentration in sweat increases according to disease severity. Sweat with elevated glucose concentration retards the recovery of the damaged skin barrier and may promote itching. This viewpoint essay outlines the relationship between sweat and itch based on recent evidence.